FUNCTIONAL-SEMANTIC CLASSIFICATION OF PROVERBS WITH NEGATIVE CONNOTATIONS IN ENGLISH, UZBEK, AND RUSSIAN (International journal of artificial intelligence, 2026)
This article analyzes theoretical and methodological issues related to the study of proverbs in modern linguistics. The proverb is considered as a complex and multifaceted linguistic unit; the problems of defining its status, linguistic nature, and functional characteristics are addressed. The paper summarizes the main approaches proposed within Russian and foreign paremiology and analyzes the key features of proverbs: anonymity, stability, brevity, generalization, metaphorical nature, and didactic orientation.It also substantiates the linguoculturological nature of proverbs and their role as units that preserve and transmit social experience in a concise form. Within the structural paremiological approach of Grigory Permyakov, the evaluative (expressive-evaluative) function of proverbs and their invariant semantic models are examined. The issues of proverb transformation and anti-proverbs are analyzed from the perspective of modern discourse. As a result, proverbs are interpreted not only as linguistic units but also as a complex phenomenon that integrates cultural, cognitive, and communicative functions.